The Impact of Transactional Leadership Style, Transformational Leadership, and Motivation on the Performance of Trade Service Employees in Palopo City - Hasrul Wijaya; Arianto Dangkeng; Muh. Ramli (Universitas Muhammadiyah Makassar, 2023)
Leadership is about how to influence other people, subordinates or followers to want to achieve the goals desired by the leader. In management science in general, there are 3 (three) models of leadership. In general, we often see these three leadership models in leaders themselves in daily practice in managing offices or companies. Each model has its own color, some arise because of God's grace, some arise very closely related to the nature or character of the person himself, some even arise as a result of the learning process. The results of this study are waiting for a saturated sample where a total population of 50 people is used as a research sample, the survey was conducted from August to September. The results of this study show that: transformational leadership style has a positive but not significant effect on employee performance, transactional leadership style has a negative but not significant effect on employee performance, motivation has a positive but not significant effect on employee performance, motivation is the dominant factor influencing leadership style, the contribution of transformational leadership, transactional leadership, and motivation on employee performance is 20%. This means that a good leadership style is one of the determining factors for employee performance.